1997
DOI: 10.1677/jme.0.0190241
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glucose transporters and hexose uptake in 3T3-L1 adipocytes: glucagon-like peptide-1 and insulin interactions

Abstract: Glucagon-like peptide-1 (7-36 amide) (GLP-1) is known to increase insulin release when given as a bolus in the fasted and fed state. GLP-1 also increases glucose uptake and lipid synthesis in cultured adipocytes. In this study we investigated the effects of GLP-1 on glucose uptake and on the levels of expression of the facilitative glucose transporters, GLUT1 and GLUT4, in fully differentiated 3T3-L1 adipocytes. Cells were incubated with GLP-1 (10 n) with or without insulin (10 and 100 n) for 24 h. Under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Thus it has been reported that membranes from human adipose tissue express GLP-1 receptors (186), and similar findings have been reported for rats (300). GLP-1 was also reported to enhance fatty acid synthesis in explants of rat adipose tissue (223) and was reported to enhance insulinstimulated glucose uptake in 3T3-L1 adipocytes (61,321). Evidence was provided, however, that the responsible receptor differed from the GLP-1 receptor (192).…”
Section: Whole Body Effects Peripheral Effects and Effects On Inmentioning
confidence: 55%
“…Thus it has been reported that membranes from human adipose tissue express GLP-1 receptors (186), and similar findings have been reported for rats (300). GLP-1 was also reported to enhance fatty acid synthesis in explants of rat adipose tissue (223) and was reported to enhance insulinstimulated glucose uptake in 3T3-L1 adipocytes (61,321). Evidence was provided, however, that the responsible receptor differed from the GLP-1 receptor (192).…”
Section: Whole Body Effects Peripheral Effects and Effects On Inmentioning
confidence: 55%
“…The utilization of a GLP-1 receptor antagonist such as exendin-(9 -39) could be useful in future studies to clarify this mechanistic and important physiological issue. The presence of GLP-1 receptors in other glucose-consuming tissues, such as skeletal muscle and adipose tissue, has also been reported (11,39,41), but the mechanism of action of GLP-1 in vitro appears to involve an enhancement of insulin's effects, since GLP-1 potentiates insulin effects on glucose transport or glycogen synthesis (20,43,44). In view of the aforementioned data and the established presence of GLP-1 receptors on peripheral tissues such as skeletal muscle, it is surprising that we were unable to detect any stimulatory effect of GLP-1 on non-HGU in our study.…”
Section: Resultsmentioning
confidence: 97%
“…Most in vitro studies show that GLP-1 stimulates glucose uptake and metabolism in muscle (24,41,44), adipocytes (20,43), and hepatocytes (2) and that GLP-1 can potentially promote glucose disposal directly, in addition to its effect on insulin secretion. In vivo, GLP-1's insulin secretion-independent effects are much less clear.…”
mentioning
confidence: 99%
“…Our results show that this loss of glucose tolerance in db/db mice was prevented, at least in part, by treatment of the mice with Ex4. Although controversial, GLP-1 has been reported to increase basal and insulin-stimulated glucose uptake [37], thus improving peripheral insulin sensitivity [8,9]. However, the possibility that Ex4 maintained normoglycaemia and improved glucose tolerance in these mice through improved peripheral insulin action was ruled out because Ex4 treatment did not change insulin sensitivity in these mice.…”
Section: Discussionmentioning
confidence: 99%